Emerging roles of traditional Chinese medicine in the treatment of diabetic gastroparesis - Zhang, Hong; You, Qianhui; Feng, Xiaohong; Qin, Zhengran (Frontiers in Nutrition, 2025)
Diabetic gastroparesis (DGP), a prevalent manifestation of diabetic autonomic neuropathy, is characterized by impaired gastrointestinal motility and delayed emptying. The pathogenesis of DGP is multifactorial, with chronic hyperglycemia serving as a key contributor through its induction of oxidative stress, inflammatory responses, immune dysregulation, and gut microbiota imbalance. These pathological processes collectively induce injury to interstitial cells of Cajal (ICCs) and gastric smooth muscle cells (GSMCs), accompanied by neuromuscular dysfunction, ultimately resulting in gastroparesis and its associated clinical symptoms. In the management of DGP, traditional Chinese medicine (TCM) offers distinct advantages, including demonstrated efficacy, favorable safety profiles, personalized treatment approaches, excellent patient tolerance, diverse dosage forms, and multi-target therapeutic effects. While the precise mechanisms remain to be fully elucidated, emerging evidence suggests that TCM may exert its beneficial effects through the protection of ICCs and GSMCs, modulation of brain-gut peptide dysregulation and neuropathy, regulation of inflammatory and immune responses, attenuation of oxidative stress, and restoration of gut microbiota homeostasis. Notably, current evidence supporting TCM for DGP leans on preclinical data with a focus on positive outcomes, whereas clinical evidence is sparse and largely limited to Chinese cohorts, reflecting the need for more clinical data and multi-cohort studies. This review comprehensively summarizes recent advances in understanding the mechanisms underlying TCM-mediated prevention and treatment of DGP, intending to provide a scientific foundation for expanding the clinical application of TCM in DGP management.